Gestational Trophoblastic Neoplasia after Ectopic Molar Pregnancy: Clinical, Diagnostic, and Therapeutic Aspects - López, Consuelo Lozoya; Lopes, Vania Gloria Silami; Resende, Fabiana Rodrigues; Steim, Jessica Lara; Padrón, Lilian; Sun, Sue Yazaki; Araujo Júnior, Edward; Braga, Antonio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
This report presents the case of a patient with gestational trophoblastic neoplasia after a partial hydatidiform mole formed in the Fallopian tube. Ectopic molar pregnancy is a rare condition, with an estimated incidence of 1 in every 20,000 to 100,000 pregnancies; less than 300 cases of it have been reported in the Western literature. The present report is important because it presents current diagnostic criteria for this rare condition, which has been incorrectly diagnosed in the past, not only morphologically but also immunohistochemically. It also draws the attention of obstetricians to the occurrence of ectopic molar pregnancy, which tends to progress to Fallopian tube rupture more often than in cases of ectopic non-molar pregnancy. Progression to gestational trophoblastic neoplasia ensures that patients with ectopic molar pregnancy must undergo postmolar monitoring, which must be just as thorough as that of patients with intrauterine hydatidiform moles, even if chemotherapy results in high cure rates.
Keywords: ectopic pregnancy; hydatidiform mole; gestational trophoblastic neoplasia; pathology